2021
DOI: 10.3390/atmos12060758
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal Forecasts of the Northern Queensland Floods of February 2019: Causes and Forecast Evaluation

Abstract: During the austral summer 2018/19, devastating floods occurred over northeast Australia that killed approximately 625,000 head of cattle and inundated over 3000 homes in Townsville. In this paper, the disastrous event was identified as a record-breaking subseasonal peak rainfall event (SPRE). The SPRE was mainly induced by an anomalously strong monsoon depression that was modulated by the convective phases of an MJO and an equatorial Rossby (ER) wave. The ER wave originated from an active equatorial deep conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…It is possible that the different hindcast periods across the S2S models present a challenge in comparing the extreme probabilities between models; however, we repeated the analysis using a common hindcast period (1999–2010) and the probability patterns remain largely unchanged (figure not shown). As detailed in recent studies, the week-long weather event that led to the extreme chill was associated with a stalling of the convective phase of the MJO over the western Pacific for ~ 10 days 1 , 15 . We next investigate whether the stalling of the MJO was predictable in the S2S models based on lead week 1 forecasts of the MJO.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…It is possible that the different hindcast periods across the S2S models present a challenge in comparing the extreme probabilities between models; however, we repeated the analysis using a common hindcast period (1999–2010) and the probability patterns remain largely unchanged (figure not shown). As detailed in recent studies, the week-long weather event that led to the extreme chill was associated with a stalling of the convective phase of the MJO over the western Pacific for ~ 10 days 1 , 15 . We next investigate whether the stalling of the MJO was predictable in the S2S models based on lead week 1 forecasts of the MJO.…”
Section: Resultsmentioning
confidence: 84%
“…Limitations on the prediction skill of the event's extreme rainfall beyond 1 week was also seen in a suite of ensemble numerical model forecasts from the UK Met Office 14 , with prediction errors generated locally in a lead week 1 forecast with convective rainfall overestimated along the western Cape York coast. This was further supported in a study focusing on a subset of four S2S models 15 , which suggested that three of the models could only predict an extreme rainfall event (off the coast of Townsville in far northeast Queensland) at a higher percentile ranking than their hindcast median, at a lead time of just over 1 week. The fourth model, on the other hand, showed good rainfall prediction skill beyond 2 weeks, which the authors argued to result from the small ensemble size ( N = 4) limiting the robustness of the statistical significance.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations